Study of Polycyclic Aromatic Hydrocarbons (PAHs) in Water of Lake Sureat - شاهين هيثم; جنيدي حسين; قره علي احمد; عطيه امال (Latakia University Journal -Engineering Sciences Series, 2021)
Determining the concentrations of polycyclic aromatic hydrocarbons (PAHs) in lake waters is very important to assess pollution and its environmental risks in this water. Therefore, in this research, water samples were collected in Lake Sureat during the whole year, and extracted and studied quantitatively and qualitatively using the technology of gas chromatography (GC-MS) in order to determine the PAHs concentrations during the seasons of the year. The results showed that the total concentrations of aromatic compounds were high in winter compared to the rest of the seasons, as its value was 508.1 ng/l. The total concentration of aromatic compounds recorded a low value in the summer, and its value was 308.47 ng/l. Some PAHs with low molecular weights (3 rings) were dominant in the water samples during the study seasons, and the total concentrations of PAHs compounds in the studied water were greater than the permissible value in drinking water sources, which poses a threat to human life.